APLIKASI PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA BUKU PENGENALAN ALAT MUSIK MODERN UNTUK ANAK - Mohamad Sofiudin; Tubagus Mohammad Akhriza; Dinny Wahyu Widarti (Jurnal Teknika, 2019)
The use of augmented reality (AR) technology as a learning medium for modern musical instruments aims to overcome the limitations of schools in terms of the procurement of musical instruments, as well as to increase the value of student understanding and provide a more interactive experience. Modern AR-based learning instruments application featuring 3D objects and 3D videos of modern musical instruments. The application is built for mobile devices operating on Android. Based on the results of testing the device, the application can run perfectly on devices with a RAM specification of 0.5 GB and above. Tests were also conducted on Diponegoro Islamic elementary school students and teachers, these students experienced an increase in understanding of modern musical instruments, while testing of teachers to measure the interactivity of applications.